ANALYSIS OF THE ELECTRICAL CONDUCTIVITY OF PVC-TIO2 NANOCOMPOSITES BY DIELECTRIC SPECTROSCOPY (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The electrical conductivity of polyvinyl chloride (PVC) and PVC-based nanocomposites and TiO2 nanoparticles with a concentration of 5% was analyzed by dielectric spectroscopy in the frequency range 10-2 - 106 Hz, for three different temperatures: 310, 320, and 340 K. The frequency variation of the imaginary part of the complex permittivity was analyzed using the Havriliak-Negami (HN) model. The influence of temperature on this variation was used to determine the activation energy of the charge carriers participating in electrical conduction in the studied materials. The frequency variation of the real part of the complex conductivity was also analyzed, and the influence of temperature on the two conductivity components, corresponding to direct current (σDC) and alternating current (σAC), was discussed in the paper. The obtained results highlight that the influence of temperature on the dielectric response, and, implicitly, on the electrical conductivity, is important, especially at low frequencies, up to 102 Hz, both for PVC and PVC-TiO2 nanocomposites. Thus, at low frequencies, from the range 10-2 - 102 Hz, there are large variations of the imaginary part of the complex permittivity with the frequency which indicates a movement of charge carriers through the polymeric material subjected to the action of the electric field. The increase in temperature leads to an increase in the values ​​of DC conductivity at low frequencies and an increase in the frequency up to which the effect of a practically frequency-independent electrical conduction is manifested.
Keywords: TiO2 nanocomposity; Dielectric spectroscopy; Electrical conductivity